GROWTH AND PRODUCTION OF PAKCOY (Brassica rapa L) ON THE MIXTMENT OF PLANTING MEDIA AND GIVING LAMTORO LEAF LIQUID ORGANIC FERTILIZER - Dora, Cyndi Maisyah; Siregar, Maimunah; Amrul, Hanifah Mutia Z. N. (Proceedings Of The International Seminar, 2023)
Pakcoy is a leaf vegetable or annual plant that can only be harvested once. To get a good production of pakcoy plants, a mixture of planting media and liquid organic fertilizer of lamtoro leaves is carried out. This study aims are to determine the response of a mixture of planting media and liquid organic fertilizer of lamtoro leaves to the growth and production of pakcoy (Brassica rapa L). The parameters observed were plant height per sample, number of plant leaves per sample, plant leaf area per sample, weight of crop production per sample, weight of crop production per plot, weight of plant consumption per sample. The results showed that the response of the administration of the planting media mixture had a very significant effect on the plant production weight parameters per plot but did not significantly affect the plant height parameters per sample, number of plant leaves per sample, plant leaf area per sample, plant production weight per sample, consumption weight plants per sample. The results of research on the application of liquid organic fertilizer of lamtoro leaves did not have a significant effect on the observed parameters. Whereas the interaction between planting media and liquid organic fertilizer of lamtoro leaves gave no significant effect on all parameters observed.   Keyword: pakcoy, growing media, POC leaf lamtoro